Trust disruption and preservation in the Covid-19 work from home context - Panteli, Niki; Nurse, Jason R. C.; Collins, Emily; Williams, Nikki (Emerald, 2022)
Purpose The paper posits that the enforced work from home (WFH) arrangement due to Covid-19 provides a unique setting for the study of trust in changing contexts. The purpose of this study, therefore, is to examine to what extent Covid-19 WFH changed trust relationships among remote employees, their managers and organisations and how this has taken place. Design/methodology/approach The study used semi-structured interviews with employees and managers from different organisations across different sectors. Interviews were supported with image prompts as suggested by the storyboarding method, and took place between November 2020 and February 2021. Thematic analysis was used to analyse the data. Findings The findings identified factors that contribute to trust disruption and factors that led to trust preservation within the changing workspace landscape enforced by WFH environment. Employees reported trust in their organisations, feeling as though their organisations proven resilient at the time of the crisis caused by the pandemic. Interestingly, managers reported trust in employees to remain productive but also anxieties due to the possible presence of others in the household. Originality/value The study identified factors that affect intra-organisational trust that have not been previously recognised, exposing tensions and challenges that may disrupt trust relations between managers and employees whilst also identifying evidence of trust preservation in the Covid-19 WFH context. The study has implications for workplace learning within the remote, WFH context, which are discussed.
Keywords: Work from home; Trust; Trust preservation; Pandemic; Remote work